Distribution of induced potential in solenoid coil - Бржезицький, Володимир Олександрович; Гаран, Ярослав Олександрович; Лапоша, Микола Юрійович (Technology audit and production reserves, 2015)
Induced magnetic field dependence of the potential for solenoid with uniform turns is considered. It is shown that the distribution of induced potential in the solenoid is nonlinear. Formulas for calculating induced potential using elliptic integrals I and type II are derived. Examples for the calculation of various length relations of solenoid to its radius (0,1 to 100) are given. The basic laws related to the distribution of induced potential in the solenoid are shown. The conditions necessary to achieve high stability characteristics of the coil in a wide frequency range are defined. In the future, similar researches are possible for multilayer coils.